Analisis Pengaruh Ukuran Maksimum Agregat Kasar Terhadap Kuat Tekan dan Porositas Pada Beton Normal - Hujiyanto, Hujiyanto; Lakawa, Irwan; Hakiman, Hakiman; Paembonan, Marhcel Yupi (Universitas Sulawesi Tenggara, 2024)
Concrete is a very popular building material used in the world of construction services, consisting of a mixture of Portland cement (PC) or other hydraulic cement, fine aggregate, coarse aggregate and water, with or without the use of additional materials that form a solid mass. This test is a research study in the laboratory by examining the materials that make up concrete including aggregate sieve analysis testing, water content testing, mud content testing, unit weight testing, aggregate specific gravity testing, coarse aggregate wear testing, slump testing and compressive strength testing, porosity testing, which is carried out according to the SNI method. Based on the results of the research carried out, it was found that the average compressive strength value of concrete for two different types of crushed stone material, for a gradation of 1-2 cm with moramo crushed stone material was 17.94 Mpa and pondidaha material was 18. 41 Mpa. And for a gradation of 2-3 cm, the average compressive strength for moramo crushed stone was 16.90 Mpa, while for pondidaha crushed stone it was 17.46 Mpa